2007
DOI: 10.1083/jcb.200606023
|View full text |Cite
|
Sign up to set email alerts
|

Type Iγ phosphatidylinositol phosphate kinase modulates adherens junction and E-cadherin trafficking via a direct interaction with μ1B adaptin

Abstract: Assembly of E-cadherin–based adherens junctions (AJ) is obligatory for establishment of polarized epithelia and plays a key role in repressing the invasiveness of many carcinomas. Here we show that type Iγ phosphatidylinositol phosphate kinase (PIPKIγ) directly binds to E-cadherin and modulates E-cadherin trafficking. PIPKIγ also interacts with the μ subunits of clathrin adaptor protein (AP) complexes and acts as a signalling scaffold that links AP complexes to E-cadherin. Depletion of PIPKIγ or disruption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
231
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(241 citation statements)
references
References 58 publications
8
231
0
Order By: Relevance
“…Indeed, it was already described by other group that the V832M mutant, besides being present at the PM as described by our group, 15 is also largely accumulated in the cytosolic compartment. 28 Our results suggest that E-cadherin structural alterations decrease the affinity of exocytic partners to bind to E-cadherin molecules. We have previously shown that a great fraction of E-cadherin mutant protein is recognized as unfolded and is degraded by the endoplasmic reticulum quality control.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 63%
See 3 more Smart Citations
“…Indeed, it was already described by other group that the V832M mutant, besides being present at the PM as described by our group, 15 is also largely accumulated in the cytosolic compartment. 28 Our results suggest that E-cadherin structural alterations decrease the affinity of exocytic partners to bind to E-cadherin molecules. We have previously shown that a great fraction of E-cadherin mutant protein is recognized as unfolded and is degraded by the endoplasmic reticulum quality control.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 63%
“…[23][24][25][26] The association of b-catenin and PIPKIg to E-cadherin cytoplasmic tail is necessary for newly synthesized E-cadherin delivery to basal-lateral membrane. 27,28 At the PM, E-cadherin molecules constitutively undergo endocytosis and can either be recycled back to the PM or be degraded. 23 The p120-catenin is the best known inhibitor of cadherin endocytosis, as its binding to the E-cadherin juxtamembrane domain is required for maintenance and stability of E-cadherin molecules at the PM and, simultaneously, it physically blocks the interaction with proteins from the endocytic machinery, such as clathrin adaptor proteins and Hakai.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in Drosophila have also shown a requirement for Cdc42, the Par6/aPKC polarity pathway and ARP2/3 to maintain normal rates of E-cadherin internalization [107]. An interaction between E-cadherin and the type Ic phosphatidylinositol phosphate kinase isoform 2 splice variant (PIPK1ci2), which links E-cadherin to the clathrin adaptor protein complex AP-1B, seems to play a role in E-cadherin endocytosis and recycling [108] as well. Internalized E-cadherin can principally be targeted for lysosomal degradation or enter the recycling pathway for redelivery to the plasma membrane.…”
Section: Trafficking Of Other Cell Surface Adhesions Proteinsmentioning
confidence: 99%